Pengaruh Derivatif Keuangan Dan Tax Avoidance Terhadap Pengungkapan Pajak Pada Perusahaan Manufaktur - Wilfon Arviant, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to verify and analyze the effect of financial derivative and tax avoidance on tax disclosure. Population in this research is manufacturing firms listed on Bursa Efek Indonesia (BEI) period of 2010-2019. By using purposive sampling method, 220 sample of 22 firms are meet the criteria of the sample. This study use secondary data which were processed using IBM SPSS Statstics 23 and SmartPLS 3 softwares. The result of this research show that financial derivative and tax avoidance have a negative effect on tax disclosure.